Seasonal variation of fatty acid profile in edible tissue of deep-sea whip lobster Puerulus sewelli (Decapoda, Palinuridae) - Chakraborty, Kajal; KRISHNAN, SOUMYA; CHAKRABORTY, REKHA DEVI; MANI, ASWATHY ELIZABETH; VIJAYAGOPAL, P. (Indian Journal of Fisheries, 2022)
Seasonal variations of the fatty acid profile of deep-sea whip lobster Puerulus sewelli (Decapoda, Palinuridae), harvestedfrom the south-west coast of India were compared. Fatty acid contents showed seasonal fluctuations, with eicosapentaenoicacid and docosahexaenoic acid being predominant during the post-monsoon and winter seasons (9-11% of cumulative fattyacids). P. sewelli was found to possess considerably higher C20-22 n-3 fatty acids during these seasons along with balancedn-3/n-6 (>2) and polyunsaturated/saturated fatty acid ratio (≥1) than those in pre-monsoon. Greater hypocholesterolemic/hypercholesterolemic ratio (>2.4) and lesser atherogenicity (